A European policy mix to address food insecurity linked to Russia's war - Georg Zachmann; Pauline Weil; Stephan von Cramon-Taubadel (Bruegel, 2022)
The Russian war against Ukraine has put at risk a significant share of global food exports, and has contributed significantly to strongly rising global food prices. This has made poor, food-import dependent countries more vulnerable, with potentially serious humanitarian consequences. The crisis also has negative security, migration and foreign policy repercussions for the European Union. The EU and its members have a number of policy levers to address the crisis. These include agricultural, trade, environment, aid, energy, fiscal and foreign policy. However, in the complex interplay of local and global, agricultural and non-agricultural markets, apparently simple solutions can have significant unintended consequences and policy trade-offs must be taken into account. While EU agricultural policy can address the crisis directly by adjusting production, energy policies also have an impact on food security through the complex relationship between the food and energy systems. Energy is an input to food production but also, as bioenergy, competes for agricultural commodities. Fiscal policy can discourage inefficient food consumption and food waste, while trade policy and aid can improve the allocation of agricultural production factors (eg fertilisers) and products. Increasing information sharing on food stocks and building trust are prerequisites for trade policy and diplomacy to limit export restrictions, thus alleviating some of the price pressures on international markets. The crisis highlights food-system fragilities when confronted with global conflicts, climate change and economic shocks. Policies should seek to increase shock-resilience, for example by reducing structural rigidities in production, trade and consumption patterns, and by encouraging sustainable production in import-dependent countries. This is especially important considering that most food production is locally consumed. Only 20 percent of the global cereals volume is traded, making the current shock significant in terms of globally traded volumes (Ukraine represents 10 percent of the global grain market), but not relative to overall volume (Ukraine represents 2 percent of global grain production).
Keywords: 330